El naciente derecho laboral mexicano: 1891-1928 - Morales Moreno, Humberto (2019)
This essay shows the ideological and doctrinal sources that prepared the way for the so-called social constitutionalism in Mexico since the end of the 19th century. Very close to the current European social issue, the Mexican liberals discussed the protection of workers and the dignity of work, disclosing free recruitment and free exercise of the profession enacted at the old article 5 of the Constitution of 1857, from subordinated and salaried work of the new article 123 of the Constitution of 1917. A mixture of libertarian and Catholic ideas and some other external influences led to the foundational and controversial debate of registering as a constitutional norm, the protection of the social and economic rights of the manufacturing and agricultural workers, which snatched judicial control, in civil matters, (which was common in other countries of America) of lawsuits arising from the recruitment, permanence and dismissal of workers, which passed to the scope of the Conciliation and Arbitration Boards under the control of the revolutionary executive of 1917. The essay shows, with original and little consulted sources, that the ideological and doctrinal influences that were behind the writing of the article of work in Mexico were in some times against the attribution of judicial law, the Amparo, in hands of the Mexican Supreme Court, despite the fact that the executive power maintained until the current reforms of 2018-2019, the control of those conciliation and arbitration boards. With the reforms of 1928 and the first Federal Labor Law of 1931, labor matters became a norm of political control of the executive power, inaugurating a kind of mass politics and unions control managed by General Cárdenas government (1934-1940).It also highlights the strong influence of the libertarian and anarchist ideas of the political newspaper Regeneration of Ricardo Flores Magón in the doctrinal body of section VI of the new article 123, which the literature known until today tends to insinuate more from the Catholic perspective of Rerum Novarum.